Adverse childhood experiences (ACEs) and Bullying Behavior Tendencies among Senior High School Students - Angelina Dyah Arum; Ridwan Rahmawan; Syafyra, Dwi Wana (Universitas Islam Negeri Raden Intan Lampung, 2025)
Bullying among adolescents remains a critical issue in educational settings, with growing evidence suggesting that adverse childhood experiences (ACEs) contribute significantly to aggressive behavior. This study aimed to examine the correlation between ACEs and bullying behavior among senior high school students. Using a quantitative correlational design, data were collected from 145 students aged 15–18 through purposive sampling. Researcher-developed Likert-type scales were used to measure ACEs and bullying behavior, with validity and reliability analyses ensuring psychometric robustness. Statistical analysis using Pearson’s product-moment correlation revealed a strong and significant positive relationship between ACEs and bullying behavior (r = .874, p < .01), with ACEs accounting for 76.3% of the variance in bullying tendencies (R² = .763). Descriptive findings further confirmed that students with higher ACE scores were more likely to engage in bullying, indicating a consistent pattern across analytical levels. These results underscore the importance of trauma-informed school interventions and early detection strategies to address the psychological roots of adolescent aggression.